Resolution of Ternary Mixture of Aspirin, Atorvastatin, and Clopidogrel by Chemometric-Assisted UV Spectroscopic and Liquid Chromatography Methods. (22nd September 2013) - Issa, Mahmoud Mohamed; Nejem, R'afat Mahmoud; Abu Shanab, Alaa; Stefan-van Staden, Raluca-Ioana
Abstract : Two chemometrics-assisted UV spectrophotometric methods were proposed for the resolution of ternary mixtures without any chemical pretreatment. The first method is based on modification of H-point standard addition method which permits simultaneous analysis of three species from a unique calibration set by making the simultaneous addition of the three analytes. Quotient between the spectra of aspirin, atorvastatin, and clopidogrel was obtained and the results showed that simultaneous determination of aspirin, atorvastatin, and clopidogrel can be obeyed in the linear range 2.5–20 μ g mL −1 of aspirin, 2.5–17.5 μ g mL −1 of atorvastatin, and 2.5–20 μ g mL −1 of clopidogrel in ternary mixture. The second method is based on the combination of the first derivative spectra and Cramer's matrix rule. In the matrix calculation, clopidogrel has zero crossing point at 316.8 and 212 nm, while for atorvastatin the zero crossing point at 250 nm where the matrix is greatly simplified and easily solved. The linear concentration ranges were 2.5–20 μ g mL −1 aspirin, 2.5–17.5 μ g mL −1 atorvastatin and 2.5–20 μ g mL −1 clopidogrel in ternary mixtures. The results proved that the simultaneous determination of aspirin, atorvastatin, and clopidogrel could be obeyed. Both methods were applied for capsules containing the three ingredients and results were in good concordance with alternative liquid chromatography.